2016
DOI: 10.1007/s11357-016-9942-x
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise increases resistance to oxidative stress in sedentary older middle-aged adults. A pilot study

Abstract: Older individuals who exercise regularly exhibit greater resistance to oxidative stress than their sedentary peers, suggesting that exercise can modify age-associated loss of resistance to oxidative stress. However, we recently demonstrated that a single bout of exercise confers protection against a subsequent oxidative challenge in young, but not older adults. We therefore hypothesized that repeated bouts of exercise would be needed to increase resistance to an oxidative challenge in sedentary older middle-ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…It has been demonstrated that the acute exercise increases resistance to oxidative stress in young but not older adults, 32 , 33 likewise that regular exercise with improved fitness leads to increased resistance to oxidative stress in older middle-aged adults. 34 However, it has also been found that chronic exercise from middle age to old age increases oxidative damage. 35 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that the acute exercise increases resistance to oxidative stress in young but not older adults, 32 , 33 likewise that regular exercise with improved fitness leads to increased resistance to oxidative stress in older middle-aged adults. 34 However, it has also been found that chronic exercise from middle age to old age increases oxidative damage. 35 …”
Section: Discussionmentioning
confidence: 99%
“…In this respect, our results show that in the study population whose activity level is moderate (4-6 METs, aerobic capacity entertains a direct relationship with energy-expenditure markers, which confirms that individuals who perform greater physical activity also have a higher energy expenditure, and consequently, their capacity for utilizing oxygen is greater, as has been noted in some other studies. 34 , 36 …”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Zarrindast et al stated that moderate-intensity aerobic training for eight weeks on the land and water reduces oxidative stress and improves antioxidant status [ 67 ]. Moreover, Done et al concluded that regular aerobic exercise increases resistance to oxidative stress [ 68 ]. Estébanez et al showed that aerobic exercise does not cause significant changes in the oxidative stress biomarkers among the elderly [ 69 ].…”
Section: The Influence Of the Physical Exercise On Oxidative Stresmentioning
confidence: 99%
“…The long-lasting effects of exercise on oxidative stress and its relationship with cardiovascular diseases is controversial, mainly because of the differences among the type, intensity, frequency and duration of the exercise programs found in the literature. Moreover, most of the studies concerned with physical exercise and related oxidative stress have concentrated on the effects of CVT [ 24 , 25 ], resistance training (RT) [ 26 ] or a combined cardiovascular and resistance training (CT) [ 18 , 27 , 28 ] on oxidative stress mainly in healthy individuals.…”
Section: Introductionmentioning
confidence: 99%